Root Anatomy and Growth of Capsicum frutescens L. on Verticulture with Different Watering Supply - Fitria Rahayu Ratmadanti; M.M. Maryani (Universitas Gadjah Mada, 2017)
The rapid increase in human population reduces land productivity in urban areas. Verticulture is a way of planting in a vertical arrangement, such as for Capsicum frutescens L. This study aimed to examine the root anatomy and growth responses of C. frutescens L. Fourteen days old seedlings were grown in polybags on the ground and into vertical pots made of paralon pipe. Watering was given for every day, once in 3 days, and once in 6 days were apllied for 35 days, at elevation of 0 cm, 25 cm, 50 cm and 75 cm. The lower watering supply decreased the root diameter due to the thinner of cortical, xylem and stele tissues. Decreased in plant height, leaf number, length-width of leaves, and fresh and dry weight of root-shoots were also observed in low watering plants, but there were increases in roots length and leaves chlorophyll content. The xylem was less developed in plants at higher position compared to the lower positon and this was more detected in plants with less watering. Decreasing plant growth occurs in conditions of water shortage and the higher plant layout on paralon, while root vascullar tissue was less developed in less watering and higher position plants.